Impact of an Assistive Device on Arm Movement Coordination in Freestyle Swimming Among Female Physical Education Students at Baghdad University - Abdulghani, Lina; Hussain, Soha (Journal of Physical Education, 2025)
The arm plays a crucial role in the freestyle swimming stroke, especially during the propulsion phase, contributing significantly to efficient movement and limb coordination. However, many learners, particularly female students at the College of Physical Education and Sport Science at Baghdad University, face difficulties mastering this skill. Traditional training methods lack immediate feedback on arm force balance and quality, limiting opportunities for simultaneous motor learning and technical improvement. To address this, a new swimming aid was developed to quantitatively measure palm pressure during swimming movements. The device includes sensors on both hands, a data processing unit, and a real-time force coordination display that provides instant biomechanical feedback. A three-month pilot study was conducted where an experimental group trained with the device, while a control group followed conventional exercises. The study aimed to evaluate the device’s effectiveness in enhancing motor coordination and propulsion force balance. Results showed a statistically significant improvement, with the experimental group’s average freestyle distance increasing from 14.125 to 20.687 meters, whereas the control group showed minimal change. The t-test confirmed the significance of these differences at p < 0.05. These findings highlight the added value of biomechanical feedback in physical education for improving motor skill performance and learning. The study provides strong evidence that this assistive device can effectively enhance swimming training techniques.